Comparative Effects of Safe Steps and Life Cycle Games on Adolescent Reproductive Literacy and Mental Health - Reni Nurhidayah; Dhita Kurnia Sari; Lingga Kusuma Wardani (Journal Of Nursing Practice, 2025)
Background: Adolescents often experience low reproductive literacy and poor mental health, which can lead to risky behaviors, early sexual debut, unintended pregnancy, and psychological problems such as anxiety and depression. Innovative approaches are needed to provide engaging and effective health education. Purpose: This study aimed to compare the effects of two educational games, SafeSteps (mobile) and LifeCycle (board game), on adolescents’ reproductive health literacy and mental health. Methods: A quasi-experimental design was applied with 266 participants divided into the two intervention groups (n=133 per group). Data on reproductive literacy and mental health (SDQ) were collected using validated questionnaires before and after the intervention. Paired t-tests and Analysis of Covariance (ANCOVA) were conducted to measure within- and between-group differences. Results: Both SafeSteps and LifeCycle significantly improved adolescents’ reproductive literacy, attitudes toward sexual violence, and mental health (p < .001). The SafeSteps group showed a significantly greater increase in reproductive literacy (mean D=17.3) compared to the LifeCycle group (mean D=13.4; F=13.84, p < .001). SafeSteps also yielded stronger gains in attitudes toward sexual violence (p < .001). Crucially, improvements in mental health were comparable between the two groups (F=1.46, p=0.228). Conclusion: SafeSteps (mobile) yielded stronger gains in cognitive and attitudinal outcomes, while both game modalities equally improved mental health. These findings recommend that policymakers and educators should integrate a hybrid approach combining scalable digital games with collaborative board-based sessions into school-based programs to ensure comprehensive and effective adolescent health promotion.